Facilitation of Fusarium graminearum Infection by 9-Lipoxygenases in Arabidopsis and Wheat - Nalam, Vamsi J.; Alam, Syeda; Keereetaweep, Jantana; Venables, Barney; Burdan, Dehlia; Lee, Hyeonju; Trick, Harold N.; Sarowar, Sujon; Makandar, Ragiba; Shah, Jyoti (Molecular plant-microbe interactions, 2015)
Fusarium graminearum causes Fusarium head blight, an important disease of wheat. F. graminearum can also cause disease in Arabidopsis thaliana. Here, we show that the Arabidopsis LOX1 and LOX5 genes, which encode 9-lipoxygenases (9-LOXs), are targeted during this interaction to facilitate infection. LOX1 and LOX5 expression were upregulated in F. graminearum–inoculated plants and loss of LOX1 or LOX5 function resulted in enhanced disease resistance in the corresponding mutant plants. The enhanced resistance to F. graminearum infection in the lox1 and lox5 mutants was accompanied by more robust induction of salicylic acid (SA) accumulation and signaling and attenuation of jasmonic acid (JA) signaling in response to infection. The lox1- and lox5-conferred resistance was diminished in plants expressing the SA-degrading salicylate hydroxylase or by the application of methyl-JA. Results presented here suggest that plant 9-LOXs are engaged during infection to control the balance between SA and JA signaling to facilitate infection. Furthermore, since silencing of TaLpx-1 encoding a 9-LOX with homology to LOX1 and LOX5, resulted in enhanced resistance against F. graminearum in wheat, we suggest that 9-LOXs have a conserved role as susceptibility factors in disease caused by this important fungus in Arabidopsis and wheat.